Endovascular repair of thoraco-abdominal aortic aneurysms in a patient with severely calcified iliac artery access and acute coronary syndrome: A case report - Duy, Le Van; Binh, Ho Anh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Thoracic and abdominal aortic aneurysms in patients with acute coronary syndrome present a rare and complex condition that remain significant diagnostic and management challenges. However, advancements in endovascular technology allow for the treatment of severe cases with minimal invasiveness, even in patients with unfavorable vascular access. In a patient presenting with acute chest pain and diagnosed with a large thoracic aortic aneurysm, abdominal aortic aneurysm, severely calcified iliac artery stenosis, and acute coronary syndrome, three critical management questions must be addressed: (1) whether to prioritize the treatment of the aortic aneurysms or acute coronary syndrome; (2) determining and optimizing the vascular access strategy for thoracic aortic Stent Graft deployment; and (3) the optimal approach to managing the abdominal aortic aneurysm with significant unilateral iliac artery stenosis. We report the successful endovascular repair of a patient with both thoracic and abdominal aortic aneurysms, severely calcified bilateral iliac artery access, and acute coronary syndrome.